Midwifery students' perspectives of physical and virtual mobility activities including preferences for e-learning: A cross-sectional survey. (February 2022) - Borrelli, S.; Walker, L.; Coolin, K.; Fumagalli, S.; Karema, A.; Konstantinidis, S.; Mets-Oja, S.; Nespoli, A.; Smit, A.-M.; Van Oost, M.; Spiby, H.
Abstract: Background: Contemporary higher education requires that all midwifery students have insight and understanding of global health practice and demonstrate intercultural sensitivity. However, the mobility models currently offered do not often fit the lives of large numbers of midwifery students. Objectives: To investigate midwifery students' international physical mobility activities and factors that affect mobility; to determine midwifery students' learning needs and preferences for related e-learning packages. Design: Multi-centre, descriptive quantitative survey. Settings: Four European Higher Education Institutions based in the United Kingdom, Estonia, Italy and the Netherlands offering an undergraduate midwifery programme. Participants: The sample included 205 midwifery students from Italy (n = 93), the Netherlands (n = 51); United Kingdom (n = 35) and Estonia (n = 26). Methods: Data were collected in June–July 2020 through an online cross-sectional, bespoke questionnaire and analysed using summary statistical analysis. Results: There is a high level of interest across a range of mobility opportunities, especially those of shorter duration. Barriers to mobility comprised finance, caring responsibilities, concerns about fitting mobility activities into the midwifery programme, negative impact on studies and language barriers. The most frequently identified facilitators of mobility included professional perspectives such as interest in other cultures and midwifery in other settings and an endorsement that mobility would add value to their development as a midwife. When engaging in virtual learning, the most preferred resources mentioned by the students were videos, video calls with peers, choice quiz and discussion forum. Conclusions: The barriers identified require new approaches to enable all midwifery students to benefit from transnational learning. The survey findings provide insights into midwifery students' perspectives from which a new mobility model can be developed. Highlights: Midwifery students are highly interested in mobility opportunities, especially those of shorter duration. Barriers to mobility are finance, caring duties, impact on studies and language barriers. Facilitators to mobility are interest in global midwifery and benefits to professional development. Videos, video calls, quizzes and forums are the preferred resources for e-learning.